Tracing the Active Phase and Dynamics for Carbon Nanofiber Growth on Nickel Catalyst Using Environmental Transmission Electron Microscopy (Small Methods 6/2022). Issue 6 (15th June 2022) - Lyu, Yiqiang; Wang, Peng; Liu, Dongdong; Zhang, Fan; Senftle, Thomas P.; Zhang, Guanghui; Zhang, Zhenyu; Wang, Jianmei; Liu, Wei
Abstract : Carbon Nanofiber Growth In article number 2200235, Senftle, Zhang, Liu, and co‐workers tracked carbon growth on a Ni catalyst via in‐situ environmental transmission electron microscopy. They found that Ni3 C particles grow carbon nanofibers through layer‐by‐layer by synchronized oscillation of tip stretch and atomic step fluctuations, which is just like the construction of a new high building.